PENERAPAN FILM SEBAGAI MEDIA PEMBELAJARAN PADA MATA KULIAH FISIKA DASAR - Asyari, Rena Amalika (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2017)
The science learning system has grown rapidly in the technology era. The aim of this researche is updating method of learning science in physics subject, so the learning system is interested of students. Film is one of media form that can be enjoyed and easy to understood by students. This research tries to explorate a film, so it can be used to learn about physical material deeply, in polytechnics. The film is the United States science documentary television series in 2014. Cosmos: A Spacetime Odyssey consists of 13 episodes that routinely shown on the National Geographic television channel. The focus of this research is many part of the 10th episode of Cosmos. The title is “The Electric Boy". This is a qualitative research with long term observation method, so it is obtained the measure of success, based on interview and student value on electricity subject.